Development of bio-rights incentive scheme for participatory restoration and conservation of mangrove resources - SRI SUHARTI (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Suharti S. 2017. Development of bio-rights incentive scheme for participatory restoration and conservation of mangrove resources. Biodiversitas 18: 121-128. Bio-rights incentive scheme is one strategy to accommodate efforts to increase economic benefits with efforts to prevent counterproductive activities to the environment (through restoration and conservation of natural resources). This study aims to assess the implementation of bio-rights incentive schemes, its achievements, and challenges in its implementation. The research was done by using survey method in Pesantren Village, Ulu Jami Sub-district, Pemalang, Central Java, Indonesia, which is the location of the pilot project established by Wetland International Indonesia (WII). The research was done in August to December 2014. The results showed that bio-rights incentives scheme could encourage the community to participate actively in restoration and conservation of mangrove resources. Implementation of bio-rights scheme was done through the provision of micro-credits to the community groups to develop activities that can generate sustainable income. Loan repayments and its interest was not in cash, but in the form of conservation service activities such as reforestation, habitat protection and the prevention of unsustainable land use. Through the bio-rights scheme, besides gaining financial benefits, villagers in Pesantren also received other benefits such as improvement of environmental conditions (widespread mangrove plantation, improvement in land productivity and the intensity of mangrove aquaculture). Keywords: Bio-rights, conservation, mangrove, participatory, restoration